Investigation of the impact of natural antioxidants found in coffee leaves, yerba mate, and jambolan pulp on the induction period and rate constant of biodiesel oxidation reaction in the presence of metallic ions - Isadora G. Branco; Julia W. Campos; Eduardo G. de Sousa; Nathan F. Silva; José Gonçales Filho; Elis Pauli; Érica S. Romagnoli; Ana C. G. Mantovani; Dionisio Borsato (Química Nova)
The present study describes the antioxidant potential of ethanolic extracts of yerba mate (Ilex paraguariensis), coffee leaves (Coffea arabica) and jambolan pulp (Syzygium cumini Lamarck) when added to biodiesel, with and without chromium (Cr3+), manganese (Mn2+) and cobalt (Co2+) metal ions, measuring the induction period (IP) and the rate constant (k) of the oxidation reaction at 110 °C. Antioxidant activity was observed in all extracts, as they reduced k and increased the IP compared to the control sample. The coffee leaves extract had the most pronounced positive effect, increasing the IP to 12.42 h and reducing k by 5.9 times. However, biodiesel containing metallic ions of chromium, manganese and cobalt, both with and without natural extracts, reduced the IP in all assays conducted in this study. The natural yerba mate extract was the most affected by the manganese ion (Mn2+), reducing the IP by 41.61%. The chromium ion (Cr3+) had the least impact on the biodiesel oxidation process in the presence of coffee leaves extract, increasing the rate constant by 3.55%. Furthermore, the alcoholic jambolan pulp extract was the one that presented the best antioxidant properties in the presence of metal ions.